7. 3x + 2y2 let x = 4, y = 3


8. (x + 2)2 - (3x - 2) - 4 Let x = 3


9. x + 2y - 3z + xyz let x = 4, y = 3, z = 2

10. xyz let x = 4, y = 2, z = 3

Respuesta :

Answer:

7. 24

8. -1

9. 28

10. 24

Step-by-step explanation:

substitute values into equations. don't forget the brackets :))

7. 3x + 2y2 Let x = 4, y = 3

= 3(4) + 2(3)2

= 12 + 12

= 24

8. (x + 2)2 - (3x - 2) - 4 Let x = 3

= ((3) + 2)2 - (3(3) - 2) - 4

= (5)2 - (9 - 2) - 4

= 10 - 9 + 2 - 4

= -1

9. x + 2y - 3z + xyz Let x = 4, y = 3, z = 2

= (4) + 2(3) - 3(2) + (4)(3)(2)

= 4 + 6 - 6 + 24

= 28

10. xyz Let x = 4, y = 2, z = 3

= (4)(2)(3)

= 24